Clownfish in hypoxic anemones replenish host O(2) at only localised scales - Herbert, N. A. (Sci Rep, 2017)
The clownfish-anemone association exemplifies a symbiosis where both members benefit from nutrient exchange and protection from predators. Clownfish also perform aeration-like behaviour in their host anemones at night, but it is not yet known whether this is stimulated by the onset of hypoxia, and whether both members benefit from O(2) replenishment. Oxygen at 3 distances above the sea anemone Entacmaea quadricolor (0.2, 1.2 and 2.2 cm) therefore was measured under 3 light levels (photon flux density = 0, 55 and 110 µmol m(−2) s(−1)), with and without the anemonefish Amphiprion frenatus. Hypoxia (O(2) < 50% air saturation) was recorded in the anemone, but only at 0.2 cm away from the anemone surface under dark conditions when A. frenatus was absent. This localised layer of hypoxia was eliminated by the presence of A. frenatus exhibiting aeration-like behaviour. Respirometry revealed that A. frenatus is extremely hypoxia tolerant (S (crit) = 14.3% at 25 °C), suggesting that aeration behaviour does not provide a major metabolic advantage to clownfish because they do not breathe water at 0.2 cm and are not metabolically constrained by O(2) at distances ≥ 1.2 cm. That the aeration behaviour of A. frenatus facilitates only the metabolism of its O(2)-conforming host reveals a unique aspect of this symbiotic relationship.